Fatigue damage evolution analysis of the CA mortar of ballastless tracks via damage mechanics-finite element full-couple method. (9th August 2021) - Deng, Shijie; Ren, Juanjuan; Wei, Kai; Ye, Wenlong; Du, Wei; Zhang, Kaiyao
Highlights: The secondary development of fatigue damage constitutive for CA mortar was conducted. A damage-finite element full-couple calculation method of CA mortar was established. Stress redistribution of CA mortar for ballastless track was caused by severe damage. 0.5 was a critical stress level to determine whether the redistribution should be taken into account. Abstract: Ballastless track withstand tens of millions or even hundreds of millions of times of train loads, its functional parts are prone to fatigue failure. In this paper, the high-cycle fatigue damage constitutive relationship of CA mortar was developed as a material subroutine, to embed into the refined FE model of CRTS-I ballastless track, establishing a damage -finite element full-couple method to analyze the influence of key factors such as void, initial deterioration and wheel load on the accumulation of fatigue damage of CA mortar. Main conclusions are as follows: void plays a more important role in the accumulation of fatigue damage of the CA mortar than initial deterioration and wheel load change. When the void length is 2.0 m, the damage value of the structure under 15 million times of wheel loads has exceeded 0.36, which is 5 orders of magnitude higher than that under the non-void condition. Laterally, the load stress below the loading point on the rail is significantly larger than at other positions, and the load stress distribution gradually gets uniformed. Along the longitudinal direction of the CA mortar, the stress at core bearing elements gradually decreases with the increase of damage, while the decreased stress is compensated by the increased stress in a certain distance from the void end along the longitudinal direction. With an initial deterioration of 50%, when the wheel load is 150 kN, the position below the rail reaches the maximum damage first, followed by the void edge, and then the damage spreads further into the middle part of the CA mortar along the lateral direction until the whole elements from the top surface at the void edge is damaged. In our study that spanned 15 million times of fatigue loading cycle, the stress level 0.5 was a critical value to determine whether the load stress redistribution caused by damage should be taken into account when using the damage - finite element full coupled method.